Sampah Plastik sebagai Ancaman terhadap Lingkungan - Muhammad Nizar Arvila Putra; Nadia Ardyta Zahrani; Tsabita Az Zahra; Berliana Clara Bella; Arsya Ghaniyyah Hariyadi; Dhea Salsa Fadhila; Sunny Akrom Al Abiyyu; Rahma Rini Khalisa Firdausi; Marchiko Naufal Justicio; Ahmad Kamalul Albar; Pandu Firmansyah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Plastic waste is one of the sources of problems for all living things, especially humans and their environment. So there is a need for awareness of this adverse impact. Measures such as the use of environmentally friendly alternatives, plastic reduction education, and government policies to limit the production and distribution of single-use plastics are increasingly being promoted. By implementing these alternative measures, it can have an impact on keeping our earth clean. The method used in this research is normative juridical, this research leads to the scientific field of law, regulations, and provisions that apply to a problem. In this case, a review of laws and regulations relating to plastic waste reduction policies is carried out. Meanwhile, the meaning of normative legal research is research conducted by looking at any library material as secondary data and is also considered as library legal research. According to the Jambeck Research Group report in 2015, Indonesia ranks second after China in the contribution of plastic waste to the ocean, with an estimated 3.2 million tons of plastic waste per year, and around 640,000-1.29 million tons end up at sea. By 2024, plastic waste in Indonesia is projected to reach around 13.98% of the total national waste generation, with an estimated volume of around 9.9 million tons. As a wise individual, we should not only rely on government policies in dealing with plastic waste, but each individual must be educated in order to create awareness of the dangers of the impact caused by the waste of plastic use.